Qualidade física de um latossolo vermelho, sob sistema de semeadura direta e cultivo convencional - de Almeida, Cinara Xavier; Jorge, Ricardo Falqueto; Centurion, José Frederico [UNESP]; Borges, Elias Nascentes; Rossetti, Karina de Vares [UNESP]; Pereira, Fabiana de Souza (My University, 2014)
The understanding and quantification of the impact of tillage systems in their physical quality are fundamental in the development of sustainable agricultural systems. This study aimed to evaluate the quality of an Oxisol under conventional tillage (CT) and no-tillage system (NT), through different physical indicators. The management systems were: CT and NT for seven or eight consecutive years (medium textured soil) and CT and NT by nine and ten consecutive years (clay soil). Were determined, at the layers 0-0.10, 0.10-0.20; 0.20-0.30 m, soil resistance to penetration, total soil porosity, macroporosity and microporosity, soil water retention, S index, soil bulk density, maximum density and relative bulk density. Was observed great variation of soil resistance to penetration throughout the soybean and corn cycles, with its highest values were found in the surface layers. The NT showed greater resistance to penetration. Among the management systems, the results against indicators of soil physical quality were similar.
Physical quality of an oxisol under no-tillage and conventional tillage
Keywords: Porosity; S index; Soil bulk density; Soil resistance to penetration; Soil water retention